Integrating Lombok’s Cultural Heritage through Digital Storytelling to Enhance EFL Students’ Speaking Skills - Rospin Hidayati; Marham Jupri Hadi; Anisa Nur’aini (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
Many EFL learners experience difficulty speaking fluently and confidently, particularly in assessment-driven learning environments. This study examined whether digital storytelling grounded in Lombok’s cultural heritage could enhance students’ speaking performance and influence their affective outcomes. Employing a mixed-methods one-group pretest–posttest design, the study involved 15 undergraduate students who participated in a four to five-week instructional intervention. Speaking performance was evaluated through digital storytelling tasks using a five-aspect analytic rubric encompassing fluency, pronunciation, grammar, vocabulary, and closing remarks. To capture learners’ experiences, qualitative data were gathered from reflective journals, focus group discussions, and field notes. The results demonstrated statistically significant improvements across all speaking dimensions. Fluency showed the greatest gain, followed by vocabulary, pronunciation, grammar, and closing remarks. Qualitative findings indicated that these improvements were supported by iterative rehearsal cycles, increased audience awareness, and culturally grounded inquiry, which facilitated more accurate lexical choices, sustained engagement, and greater confidence. The study provides empirical evidence that locally anchored digital storytelling functions not merely as contextual enrichment but as a pedagogical design principle for speaking instruction. Theoretically, the findings are framed through an integrated perspective drawing on Communicative Language Teaching, Sociocultural Theory, and Self-Determination Theory. Pedagogically, the study recommends adopting culturally grounded digital storytelling as a core speaking cycle, supported by targeted focus-on-form activities and calibrated analytic assessment rubrics.